PENINGKATAN HASIL BELAJAR SENI MUSIK DENGAN MEDIA AUDIO VISUAL MELALUI METODE BERVARIASI (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2010)
students are less interested in learning the art of music. Moreover, the way the teacher teaches are not so attractive, complementing the students' reasons to override music art. This research is a class action research conducted in two cycles. Cycle I and Cycle II consist of planning, action observation and reflection. Data collection was done through tests, observations, interviews and documentation. Data were analyzed descriptive quantitatively and qualitatively. Based on data analysis, it is concluded that audiovisual media and varied methods improve learning outcomes of music lesson after the action of the first cycle, 84% of students reached a value greater than or equal to 64. In the second cycle, the percentage increased to 88%. Changes in behavior in this study were the students seemed happy, more motivated in learning, enthusiastic in asking questions, and pay full attention to teachers' explanation. Considering the result of the study, the researcher suggests teachers use audiovisual media and a variety of methods to generate students’ interest and attraction in appreciating the art of local music.Kata kunci: hasil belajar, media audio visual, metode bervariasi.